2006
DOI: 10.1182/blood-2006-08-040196
|View full text |Cite
|
Sign up to set email alerts
|

The Slc35d3 gene, encoding an orphan nucleotide sugar transporter, regulates platelet-dense granules

Abstract: Platelet dense granules are lysosomerelated organelles which contain high concentrations of several biologically important low-molecular-weight molecules. These include calcium, serotonin, adenine nucleotides, pyrophosphate, and polyphosphate, which are necessary for normal blood hemostasis. The synthesis of dense granules and other lysosomerelated organelles is defective in inherited diseases such as Hermansky-Pudlak syndrome (HPS) and Chediak-Higashi syndrome (CHS). HPS and CHS mutations in 8 human and at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 37 publications
2
52
1
Order By: Relevance
“…However, it was more highly expressed in adipose tissues compared to other tissues, including heart, liver, and kidney. In the mouse, SLC35D3 is primarily expressed in the liver and kidney compared with other organs, but not in adipose tissues [20]. Based on our results, we conclude that SLC35D3 may have an important function in adipose tissue.…”
Section: Expression Of Slc35d3 In Adipose Tissues From Different Varimentioning
confidence: 60%
See 2 more Smart Citations
“…However, it was more highly expressed in adipose tissues compared to other tissues, including heart, liver, and kidney. In the mouse, SLC35D3 is primarily expressed in the liver and kidney compared with other organs, but not in adipose tissues [20]. Based on our results, we conclude that SLC35D3 may have an important function in adipose tissue.…”
Section: Expression Of Slc35d3 In Adipose Tissues From Different Varimentioning
confidence: 60%
“…A recent study found that obesity is not only caused by abnormal metabolism, Li Wei research group found that the SLC35D3 protein was participate in fat deposition, meanwhile it is involved in the neural regulation process, and this is the first report about metabolic disorder caused by unusual central behavior not due to endocrine disorders. SLC35D3 localizes on mouse chromosome 10 and regulates platelet-dense granule content [20]. In the human, the SLC35D3 gene, which localizes on chromosome 6 close to the D6S1009, its mutation can cause obesity, it is a candidate gene for MetS [19].…”
Section: Expression Of Slc35d3 In Adipose Tissues From Different Varimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that SLC35D3 is involved in the biogenesis of platelet dense granules. 20,21 Moreover, Slc35d3 is specifically expressed in the substantia nigra (SN), striatum, and olfactory bulb in mouse brain. 22 It functions as an ER chaperone for DRD1 (dopamine receptor D1) trafficking to the plasma membrane of the medium spiny neurons in the striatum.…”
Section: Introductionmentioning
confidence: 99%
“…20 SLC35D3 is predicted to be an orphan nucleotide sugar transporter or a fringe connection-like protein with 10 transmembrane domains. It has been reported that SLC35D3 is involved in the biogenesis of platelet dense granules.…”
Section: Introductionmentioning
confidence: 99%